Muscle Loss During Androgen Deprivation Therapy Is Associated With Higher Risk of Non-Cancer Mortality in High-Risk Prostate Cancer - Chiang, Pai-Kai; Tsai, Wei-Kung; Chiu, Allen Wen-Hsiang; Lin, Jhen-Bin; Yang, Feng-Yi; Lee, Jie (Frontiers in Oncology, 2021)
The changes in body composition are early adverse effects of androgen deprivation therapy (ADT); however, their prognostic impact remains unclear in prostate cancer. This study aimed to evaluate the association between body composition changes and survival in patients with high-risk prostate cancer. We measured the skeletal muscle index (SMI) and total adipose tissue index (TATI) at the L3 vertebral level using computed tomography at baseline and within one year after initiating ADT in 125 patients with high-risk prostate cancer treated with radiotherapy and ADT between 2008 and 2018. Non-cancer mortality predictors were identified using Cox regression models. The median follow-up was 49 months. Patients experienced an average SMI loss of 5.5% over 180 days (95% confidence interval: -7.0 to -4.0; p<0.001) and TATI gain of 12.6% over 180 days (95% confidence interval: 9.0 to 16.2; p<0.001). Body mass index changes were highly and weakly correlated with changes in TATI and SMI, respectively (Spearman ρ for TATI, 0.78, p<0.001; ρ for SMI, 0.27, p=0.003). As a continuous variable, each 1% decrease in SMI was independently associated with a 9% increase in the risk of non-cancer mortality (hazard ratio: 1.09; p=0.007). Moreover, the risk of non-cancer mortality increased 5.6-fold in patients with SMI loss ≥5% compared to those with unchanged SMI (hazard ratio: 5.60; p=0.03). Body mass index and TATI were not associated with non-cancer mortality. Muscle loss during ADT is occult, independent of weight change, and independently associated with increased non-cancer mortality in patients with high-risk prostate cancer.